2018
DOI: 10.1039/c8fo00547h
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer potential against cervix cancer (HeLa) cell line of probiotic Lactobacillus casei and Lactobacillus paracasei strains isolated from human breast milk

Abstract: Lactic acid bacteria have been categorized as probiotics and play a crucial role in human health by stimulating the supply of nutrients, shaping the immune system, and preventing the colonization of pathogenic microbes. This study investigated the mechanisms for the action of three potential probiotic Lactobacillus strains: Lactobacillus casei SR1, Lactobacillus casei SR2, and Lactobacillus paracasei SR4 isolated from human breast milk. These Lactobacillus strains were identified via 16S DNA sequencing and cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(53 citation statements)
references
References 49 publications
2
51
0
Order By: Relevance
“…Western blotting for the detection of apoptosis‐related proteins also revealed that the population of apoptotic cells and the cleaved forms of caspase‐9 and PARP were markedly increased in cells treated with the 3‐day FBE, more than those treated with 7‐day FBE (Figure D). The degree of apoptosis caused by FBE did not depend on the fermentation time of the treated blueberries, which can be explained by the fact that probiotic lactobacillus strains themselves could inhibit proliferation and induce apoptosis in cervical cancer cells (Rajoka et al., ). In our study, lactobacillus growth was most prominent on the third day of blueberry fermentation, and the apoptosis of HeLa cells was also increased most when treated with 3‐day FBE.…”
Section: Resultsmentioning
confidence: 99%
“…Western blotting for the detection of apoptosis‐related proteins also revealed that the population of apoptotic cells and the cleaved forms of caspase‐9 and PARP were markedly increased in cells treated with the 3‐day FBE, more than those treated with 7‐day FBE (Figure D). The degree of apoptosis caused by FBE did not depend on the fermentation time of the treated blueberries, which can be explained by the fact that probiotic lactobacillus strains themselves could inhibit proliferation and induce apoptosis in cervical cancer cells (Rajoka et al., ). In our study, lactobacillus growth was most prominent on the third day of blueberry fermentation, and the apoptosis of HeLa cells was also increased most when treated with 3‐day FBE.…”
Section: Resultsmentioning
confidence: 99%
“…62 Importantly, it was previously found that certain Lactobacillus strains isolated from human breast milk could combat cervical cancer via inducing apoptosis and inhibiting proliferation. 63 In particular, L. casei potentiated the antiproliferative effect of geniposide through the production of b-glucosidase in oral squamous cell carcinoma. 64 Remarkably, the anti-cancer activity of inulin was previously elucidated against melanoma as well as the transplanted mammary tumors in rats.…”
Section: Discussionmentioning
confidence: 98%
“…Several in vitro experiments have revealed that probiotic bacteria demonstrate cytotoxicity against human cancer cell lines [13,14]. Viable bacteria, metabolites [15] and cell free extracts [16] have been proposed as anti-proliferative agents.…”
Section: Introductionmentioning
confidence: 99%